REVITALISASI KURIKULUM PESANTREN (Studi Kasus di Pondok Pesantren Al Iman Putri, Babadan, Ponorogo) - Mukhlas, Moh (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2013)
Female Islamic Boarding school of Al Iman is one of Islamic educational institutions that always make significant innovation and revitalization of its education system. It has revitalized the curriculum by adapting and combining the four well-established curricula, such as KMI Gontor, Ministry of Religious Affairs, Ministry of National Education, and the Salafi Islamic School. This study was aimed to examine the three issues about revitalization of the education system, they were: ( 1 ) reasons to revitalize the curriculum, ( 2 ) process of revitalization, and ( 3 ) the challenges and response of the revitalization of the curriculum.Â Â Â Â Â Â Â Â Â Â Â  In order to answer those problems, qualitative method was occupied by applying interview, observation, and documentation to gain the data needed. Additionally, the collected data were analyzed by using analytical models developed by Spreadly.Â Â Â Â Â Â Â Â Â Â Â  The results revealed that: firstly, the ultimate reason of revitalizing the curriculum was to complement the curriculum of KMI Gontor that had become its main reference, get some advantages from the point of curriculum derived from Ministry of Religious Affairs, Ministry of National Education, and Salafi Islamic School, as well as to create qualified alumnus that were recognized by government and society. Secondly, this revitalization was done in several stages, they were (a) reviewing and analyzing curriculum, (b) preparing human resources, and (c) executing, implementing and evaluating the curriculum. Thirdly, the challenges were revealed, such as: (a) the difference views among the leaders, (b) the need of different teaching hours among teachers, and (c) the density of student activity. In order to respond these challenges, there were some important things to do, such as (a) mutual understanding and harmonization,Â  (b) provide additional teaching hours, and (c) provide activities to refresh studentsâ mentality.Â ÙØ¹ÙØ¯ Ø§ÙØ¥ÙÙØ§Ù ÙÙØ¨ÙØ§Øª Ø¥ØØ¯Ù Ø§ÙÙØ¤Ø³Ø³Ø§Øª Ø§ÙØªØ±Ø¨ÙÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙØªÙ ØªØØ§ÙÙ â Ø¯Ø§Ø¦ÙØ§ â Ø¹ÙÙÙØ© Ø§ÙØ§Ø¨ØªÙØ§Ø± ÙØ§ÙØªÙØ´ÙØ· ÙÙ ÙÙÙØ¬ ØªØ±Ø¨ÙØªÙ. Ø§Ø¨ØªÙØ± Ø§ÙÙØ¹ÙØ¯ ÙÙØ´ÙØ· Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù ÙÙ Ø¨Ø§ÙØ¬ÙØ¹ Ø¨ÙÙ Ø£ÙÙØ§Ø¹ Ø§ÙÙÙØ§ÙØ¬Ø ÙÙ Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù ÙÙØ¹ÙØ¯ Ø¯Ø§Ø± Ø§ÙØ³ÙØ§Ù ÙÙÙØªÙØ±Ø ÙÙÙØ²Ø§Ø±Ø© Ø§ÙØ´Ø¤ÙÙ Ø§ÙØ¯ÙÙÙØ©Ø ÙÙÙØ²Ø§Ø±Ø© Ø§ÙØªØ±Ø¨ÙØ©Ø ÙÙÙÙØ¹ÙØ¯ Ø§ÙØ³ÙÙÙ. ÙÙØ¯Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø¥ÙÙ Ø¨ÙØ§Ù Ø«ÙØ§Ø«Ø© Ø£Ø´ÙØ§Ø¡ ÙÙ Ø¹ÙÙÙØ© Ø§ÙØªÙØ´ÙØ· ÙÙ ÙØ¸Ø§ÙÙ Ø§ÙØªØ±Ø¨ÙÙØ ÙÙÙ: 1) Ø£Ø³Ø¨Ø§Ø¨ ØªÙØ´ÙØ· Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³ÙØ 2) Ø¹ÙÙÙØ© Ø§ÙØªÙØ´ÙØ·Ø 3) Ø§ÙØªØØ¯ÙÙØ§Øª ÙØ§ÙØ§Ø³ØªØ¬Ø§Ø¨Ø§Øª ÙØ¹ÙÙÙØ© Ø§ÙØªÙØ´ÙØ·. ÙÙÙØ¥Ø¬Ø§Ø¨Ø© Ø¹Ù Ø£Ø³Ø¦ÙØ© Ø§ÙØ¨ØØ«Ø Ø§Ø³ØªØ®Ø¯Ù Ø§ÙØ¨Ø§ØØ« Ø§ÙÙÙÙØ¬ Ø§ÙÙÙÙÙØ ÙÙÙØØµÙÙ Ø¹ÙÙ Ø§ÙØ¨ÙØ§ÙØ§Øª Ø§Ø³ØªØ®Ø¯Ù Ø§ÙØ£Ø¯ÙØ§Øª : Ø§ÙÙÙØ§Ø¨ÙØ© ÙØ§ÙÙÙØ§ØØ¸Ø© ÙØ§ÙÙØ«Ø§Ø¦Ù Ø§ÙÙÙØªÙØ¨Ø©. ÙØ£ÙØ§ ÙØªØÙÙÙ Ø§ÙØ¨ÙØ§ÙØ§Øª Ø§Ø³ØªØ®Ø¯Ù Ø§ÙØ£Ø³ÙÙØ¨ ÙØ³ÙØ±ÙØ¯ÙÙ. ÙØ£ØªÙ Ø§ÙØ¨ØØ« Ø¨Ø§ÙÙØªØ§Ø¦Ø¬ Ø§ÙØªØ§ÙÙØ© : 1) Ø£Ø³Ø¨Ø§Ø¨ ØªÙØ´ÙØ· ÙØ°Ø§ Ø§ÙÙÙÙØ¬ ÙÙ Ø¥ÙÙØ§Ù Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù ÙÙØ¹ÙØ¯ "Ø¯Ø§Ø± Ø§ÙØ³ÙØ§Ù " ÙÙØØµÙÙ Ø¹ÙÙ Ø§ÙØ£ÙØ¶ÙÙØ© ÙÙ Ø§ÙÙÙÙØ¬ ÙÙØ²Ø§Ø±Ø© Ø§ÙØ´Ø¤ÙÙ Ø§ÙØ¯ÙÙÙØ©Ø ÙÙÙØ²Ø§Ø±Ø© Ø§ÙØªØ±Ø¨ÙØ©Ø ÙÙÙÙØ¹ÙØ¯ Ø§ÙØ³ÙÙÙ. 2) ÙÙØ°Ø§ Ø§ÙØªÙØ´ÙØ· ÙÙØ± Ø¨ÙØ±Ø§ØÙ : Ø£) Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙØªØÙÙÙ Ø§ÙÙÙÙØ¬Ø Ø¨) Ø¥Ø¹Ø¯Ø§Ø¯ Ø§ÙÙÙØ§Ø±Ø¯ Ø§ÙØ¨Ø´Ø±ÙØ©Ø Ø¬) ÙØ±ØÙØ© Ø§ÙØªÙÙÙØ° ÙØ§ÙØªØ·Ø¨ÙÙ Ø«Ù Ø§ÙØªÙÙÙÙØ Ø¯) 3.) Ø£ÙØ§ Ø§ÙØªØØ¯ÙØ§Øª Ø§ÙØªÙ ÙÙØ§Ø¬ÙÙØ§ Ø§ÙÙØ¹ÙØ¯ : Ø£) Ø§Ø®ØªÙØ§Ù Ø§ÙØ¢Ø±Ø§Ø¡ Ø¨ÙÙ Ø§ÙØ±Ø¤Ø³Ø§Ø¡Ø Ø¨) ÙØ¬ÙØ¯ Ø¹Ø¯Ù Ø§ÙØªÙØ§ÙÙ Ø¨ÙÙ ØØ§Ø¬Ø§Øª Ø§ÙØØµØµ ÙÙÙØ¯Ø±Ø³ÙÙØ Ø¬) ÙØ«Ø±Ø© ÙØªÙÙØ¹ Ø£ÙØ´Ø·Ø© Ø§ÙØ·Ø§ÙØ¨Ø§Øª. ÙÙØ§Ø³ØªØ¬Ø§Ø¨Ø§Øª ÙØ°Ù Ø§ÙØªØØ¯ÙØ§Øª Ø¹ÙÙØª Ø§ÙØ£ÙÙØ± : Ø£) Ø§ÙØªÙØ§ÙÙ Ø¨ÙÙ Ø§ÙØ£ÙØ±Ø§Ø¯Ø Ø¨) Ø¥Ø¹Ø·Ø§Ø¡ Ø²ÙØ§Ø¯Ø© Ø§ÙØØµØ© Ø Ø¬) ØªÙØ´ÙØ· Ø±ÙØÙØ© Ø§ÙØ·Ø§ÙØ¨Ø§Øª.